Can the present be absent?

Calculus Level 4

E = 0 x 2015 ( 1 + x ) 2017 d x \mathscr{E} = \displaystyle \int_{0}^{\infty} \dfrac{x^{2015}}{(1+x)^{2017}} \, dx

If E \mathscr{E} can be represented in the form a b \dfrac{a}{b} , with a , b a, b being positive coprime integers, find a + b a + b .


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Rishabh Jain
Jun 16, 2016

Substitute x = tan 2 θ \small{\color{#D61F06}{x=\tan^2\theta}} such that d x = 2 tan θ sec 2 θ d θ = 2 sin θ d θ cos 3 θ \small{\color{#D61F06}{\mathrm{d}x=2\tan \theta\sec^2 \theta ~\mathrm{d}\theta=\dfrac{2\sin \theta~\mathrm{d}\theta}{\cos^3\theta}}} so that ( Also use 1 + tan 2 θ = 1 cos 2 θ ) \left(\small{\text{Also use }\color{#69047E}{1+\tan^2\theta=\dfrac1{\cos^2\theta}}}\right) :

E = 2 0 π / 2 sin 4031 θ cos θ d θ d ( sin θ ) \mathscr{E}=2\displaystyle\int_0^{\pi/2}\sin^{4031}\theta~ \underbrace{\cos \theta~\mathrm{d}\theta}_{\mathrm{d}(\sin \theta)}

= [ 2 sin 4032 θ 4032 ] 0 π / 2 = 1 2016 \large =\left[\dfrac{2\sin^{4032}\theta}{4032}\right]_0^{^{\pi/2}}=\boxed{\dfrac1{2016}}

1 + 2016 = 2017 \Large \therefore 1+2016=\boxed{\color{#007fff}{2017}}


ALT: E = 0 1 x 2 d ( 1 + 1 x ) ( 1 + 1 x ) 2017 d x \small{\color{grey}{\text{ALT: }}}\large\mathscr{E} = -\displaystyle \int_{0}^{\infty} \dfrac{\overbrace{\frac{-1}{x^2}}^{\mathrm{d}\left(1+\frac 1x\right)}}{\left(1+\frac 1x\right)^{2017}} \mathrm{d}x

= [ ( 1 + 1 x ) 2016 2016 ] 0 = 1 2016 \large = \left[\dfrac{\left(1+\frac 1x\right)^{-2016}}{2016}\right]_0^{\infty}=\boxed{\dfrac1{2016}}

I used the beta function. I like your solution though!

Hobart Pao - 4 years, 12 months ago

β ( a , b ) = 0 x a 1 ( 1 + x ) a + b \displaystyle \beta(a,b)=\int_{0}^{\infty} \frac{x^{a-1}}{(1+x)^{a+b}}

So our integral equals = β ( 2016 , 1 ) = Γ ( 2016 ) Γ ( 1 ) Γ ( 2017 ) = 1 2016 \displaystyle \beta(2016,1) = \frac{\Gamma(2016)\Gamma(1)}{\Gamma(2017)} = \frac{\color{#D61F06}{1}}{\color{#3D99F6}{2016}}

So answer is : 1 + 2016 = 2017 \boxed{1+2016=2017}

Akash Shukla
Jun 17, 2016

I = 0 x 2015 ( 1 + x ) 2017 d x = I=\displaystyle∫_{0}^{\infty} \dfrac{x^{2015}}{(1+x)^{2017}} dx= 0 x 2017 ( 1 + x ) 2017 x 2 = \displaystyle∫_{0}^{\infty}\dfrac{x^{2017}}{(1+x)^{2017}*x^2}= 0 1 ( 1 x + 1 ) 2017 x 2 d x \displaystyle∫_{0}^{\infty}\dfrac{1}{(\dfrac{1}{x}+1)^{2017}*x^2}dx

Now Let 1 x = t \dfrac{1}{x} = t

I = 0 1 ( t + 1 ) 2017 d t = I = \displaystyle∫_{0}^{\infty} \dfrac{1}{(t+1)^{2017}}dt=

1 2016 [ 1 ( t + 1 ) 2016 ] 0 = \displaystyle\dfrac{-1}{2016}\large \left[\dfrac{1}{(t+1)^{2016}}\right]_{0}^{\infty} =

1 2016 ( 0 1 ) = 1 2016 = a b \displaystyle\dfrac{-1}{2016}(0-1) = \dfrac{1}{2016}= \dfrac{a}{b}

Therefore, a + b = 1 + 2016 = 2017 a+b = 1+2016=2017

Kushal Bose
Jun 16, 2016

Also one can put z=1+(1/x)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...